(untitled) (Bangladesh Journal of Psychiatry, 2017)
The symptoms of conversion disorder arise in response to stressful situations. The objective of the study was to evaluate the frequency of various psychosocial stressors and socio-demographic characteristics in patients with Conversion disorder. This was a descriptive Cross sectional study conducted in the Department of Psychiatry of Jalalabad Ragib Rabeya Medical College Hospital, Sylhet, Bangladesh during the period from March 2011 to February 2013 among 240 admitted patients with conversion disorder satisfying inclusion and exclusion criteria who were consecutively selected as study group. This study revealed that the most of the patients (62.5%) were below the age of 25 years with female predominance (90.4%). Among the patients, 67.5% came from joint family, 62.1% from rural area and 71.7% from the families with income within 10,000-20,000 BDT per month. Also 62.5% patients experienced seizure whereas 22.9% experienced mixed symptoms. Psychosocial stressors were clearly identified in 87.5% of the patients. The stressors in our population in order of frequency were disturbed relation with in-laws (20.8%), failure in examination or study problem (20%), disturbed relation with spouse (15.4%), husband staying abroad (13.3%), love problems (11.2%), job stress or more work-load (11.2%), relationship problem with family members or parents (9.6%), pampered child (3.3%), demand of marriage (3.3%), marriage against will (2.9%), death of a close family member (2.1%), physical illness (2.1%), demand of going abroad (1.7%), issue less (1.7%) and financial crisis (1.2%). In this study, a large number of stressors were identified in patients with conversion disorder. The pattern of the stressors in our subjects was unique to our population and most of these stressors were easily treatable. Bang J Psychiatry Dec 2014; 28(2): 41-44